EFFECT OF WORK LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEES JOB SATISFACTION IN THE NURSING DEPARTMENT AT MITRA SEJATI GENERAL HOSPITAL MEDAN - Audrey Wulandari; Nana Dyki Dirbawanto (Transpublika Publisher, 2022)
This study aims to determine and analyze the effect of work-life balance and the work environment on employee job satisfaction in the nursing department of Mitra Sejati General Hospital Medan. This study uses an associative research method with a quantitative approach. The study population was 530 staff from Mitra Sejati General Hospital in Medan. Research sample consist of 85 nurses which obtained by purposive sampling. Direct distribution of a Likert-scaled questionnaire is used for data collection. The method of data analysis utilized an instrument test of validity, reliability, a classical assumption test, and a hypothesis test utilizing multiple linear regression analysis assisted by SPSS version 25. Based on the findings of the study, the work-life balance variable has a partial effect on job satisfaction, as indicated by t-statistic 4,447 > t-table 1,633. As indicated by the value of t-statistic 3,242 > t-table 1,633, the work environment variable has a partial effect on job satisfaction. Based on simultaneous testing, work-life balance and work environment has a simultaneous influence on job satisfaction variable with a value of F-statistic 7,277 > F-table 3,11, a R value of 0,588 and an Adjusted R Square value of 33%, while the remaining 67% is influenced by other factors not examined in this study.